Unraveling Plastic Pollution in Protected Terrestrial Raptors Using Regurgitated Pellets - Chloe Wayman; Francisca Fernández-Piñas; Irene López-Márquez; Rocío Fernández-Valeriano; Juan José Iglesias-Lebrija; Fernando González-González; Roberto Rosal; Miguel González-Pleiter (Microplastics)
The threat of plastic pollution has escalated to unprecedented levels, with particular concern surrounding microplastics (MPs) and artificial fibers or particles (AFs) due to their wide distribution across ecosystems and their bioavailability to wildlife. Although research on the impact of plastic on wild birds is rapidly growing, knowledge of terrestrial species remains limited, especially regarding raptors, which have been significantly understudied. Here, we investigated the prevalence of MPs and AFs in regurgitated pellets from six protected terrestrial raptor species, namely the Cinereous Vulture (Aegypius monachus), the Bonelli’s Eagle (Aquila fasciata), the Little Owl (Athene noctua), the Lesser Kestrel (Falco naumanni), the Red Kite (Milvus milvus), and the Barn Owl (Tyto alba), collected between 2022 and 2023. Our analysis revealed that 68% of the pellets contained MPs (47 out of 69), and 81% contained AFs (56 out of 69). Additionally, two macroplastics were found inside the pellets: a cable tie in a Red Kite and a bird identification ring in a Cinereous Vulture. The concentrations (mean ± standard error of the mean) were 2.39 ± 0.39 MPs/pellet and 5.16 ± 0.72 AFs/pellet. The concentration of MPs and AFs varied significantly among some of the studied species; however, no significant differences were observed among urban, rural, and protected areas. This could indicate that contamination levels are mainly related to the type of species. Fibers emerged as the predominant contaminant shape, with six different polymers identified, among which PET, PE, and acrylics were the most prevalent. These findings highlight that plastic pollution has reached protected terrestrial raptors and that the impact of plastic on their life cycles needs to be assessed.